Development of Project-Based Learning (PjBL)-Based Learning Videos on Green Chemistry Materials Oriented to Student Learning Motivation - Jaspiya jaspiya; Haryanto Haryanto; Febbry Romundza; Rayandra Asyhar; Kriswantoro Kriswantoro; Firdiawan Ekaputra (Universitas Khairun, 2026)
Learning videos are one of the digital learning media that can support a more interesting and meaningful learning process. In green chemistry material, students are required to understand the concept of applying chemical principles in daily life and have concern for the environment. However, the learning process that still uses a less varied approach causes low student motivation to learn. This study aims to develop a Project Based Learning (PjBL)-based learning video on green chemistry material, determine the feasibility level of learning videos based on the assessment of material experts, media experts, and teacher assessment, and determine students’ responses to the develop learning videos from the student’s learning motivation. This research is a developmental research using the Lee & Owens model. The research instruments used included interview sheets, validation questionnaires for material experts and media experts, teacher assessment questionnaires, and student response questionnaires. The product developed was validated by material experts and media experts, then assessed by teachers and tested in small group trials. The data analysis teachniques used are qualitative data analysis and quantitative data analysis. The results of the study showed that the Project Based Learning (PjBL)-based learning video on green chemistry materials obtained a validation percentage of material experts of 90% and media experts of 92% with the category of